Experimental investigation of Paper Honeycomb subjected to quasi-static loading - M. R, Said; M.K., Ismail (2012)
Three point bending test is performed to investigate the collapse load of paper honeycomb sandwich panel. Three panel thickness were considered; 9.1 mm, 35.84 mm and 41.92 mm with an eight span length. Eight span lengths range from 50 mm to 120 mm with 10 mm increment are compressed with 2 mm/min. The Paik’s theoretical collapse load is adapted and compared with experimental results.The agreement between experiment and theory are only found at d= 50mm,70 mm and 120 mm.